2021
DOI: 10.4236/ce.2021.124055
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Interactive Online Tool (Plickers) in Learning Vocabulary among Young Learners in ESL Setting

Abstract: Technology is proven to be one of the factors supporting teaching and learning in the classroom in this digital age. Teachers are also encouraged to use technical resources to enhance the language skills of students in ESL classrooms. The aim of this research is to reveal the perceptions and motivation of students about the use of Plickers in learning ESL vocabulary. Embedded design from mixed method research was selected as the research method to achieve this aim. The survey questionnaire was answered by 50 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
1
Order By: Relevance
“…As for English language, a number of vital skills that needs to be taught to the students, which includes speaking and writing abilities, compositions and creativity through the activities or tools provided (Richards & Rodger, 2014). In conjunction with this, a variety of strategies and techniques has to be applied as the ESL teaching and learning will only take place when the ESL students are around (Hassan & Hashim, 2021). Thus, stepping and living on this digital era, the technology has been widely utilized in the English language class in order to build up the essential English skills among the ESL students.…”
Section: Esl Teaching + Technologymentioning
confidence: 99%
“…As for English language, a number of vital skills that needs to be taught to the students, which includes speaking and writing abilities, compositions and creativity through the activities or tools provided (Richards & Rodger, 2014). In conjunction with this, a variety of strategies and techniques has to be applied as the ESL teaching and learning will only take place when the ESL students are around (Hassan & Hashim, 2021). Thus, stepping and living on this digital era, the technology has been widely utilized in the English language class in order to build up the essential English skills among the ESL students.…”
Section: Esl Teaching + Technologymentioning
confidence: 99%
“…Sugiyono (2018) mendefinisikan studi literatur sebagai analisis teoritis serta referensi lainya yang terkait dengan nilai, budaya, dan norma yang muncul dalam situasi sosial yang sedang diteliti. Cresswell (2018) dalam (Hassan & Hashim, 2021) menjelaskan bahwa studi literature adalah sintesis tertulis dari penelitian terdahulu, buku, serta referensi yang menjelaskan teori terkait dengan topik dan dokumen yang relevan. Dalam pengumpulan data, dilakukan dengan mengevaluasi berbagai jenis literatur, seperti buku, jurnal penelitian, disertasi, e-book, dan contoh-contoh kasus yang berkaitan dengan masalah yang sedang diteliti.…”
Section: Metodeunclassified
“…Regarding learning attitude, Wiyaka and Prastikawati (2021) integrated the Plickers into the English class, and reported that the Plickers might advance student English learning. In Hassan and Hashim’s (2021) study, Plickers was adopted for supporting student vocabulary learning. The findings indicated that Plickers had a positive impact on students’ perceptions.…”
Section: Background Informationmentioning
confidence: 99%